Ethnobotanical study of underutilized wild edible plants and threats to their long-term existence in Midakegn District, West Shewa Zone, Central Ethiopia - Sheleme Guzo; Ermias Lulekal; Sileshi Nemomissa (BMC, 2023)
Abstract Background Ethiopia is endowed with much plant diversity. The insignificant number of studies on wild edible plants with their ethnobotanical perspectives indicated that this plant diversity comprised only hundreds of wild edible plants used to supplement food sources for the local community under different conditions. There still need to be further investigations throughout the country when compared to the total area and cultural diversity of the country. However, they are seriously under pressure due to different natural and human influences. Therefore, the study was conducted to document underutilized wild edible plants along with their associated indigenous knowledge and explore threats to them in Midakegn District. Methods A questionnaire survey, semi-structured interviews, a market survey, score ranking, and focused group discussions were employed for data collection. Statistical analysis of ethnobotanical knowledge mean variation between different informant groups was computed by using one-way ANOVA in the IBM SPSS Statics version 24 package. Results A total of fifty underutilized wild edible plants belonging to 39 genera and 30 families were collected, recorded, and documented. The families Moraceae (four), Fabaceae, Flacourtaceae, Myrtaceae, Rosaceae, and Tiliaceae (each three) represented the highest number of species. It comprised shrubs (44%), trees (36%), herbs (18%), and epiphytes (2%). Fruits (62.3%) were found to be the most frequently used and mostly taken raw, fresh, or dried. These edible resources were consumed to supplement staple foods (67.3%), whereas 25% were used as emergency foods. The majority of species (96%) had multiple uses in addition to their edibility. A significantly higher (P < 0.05) number of underutilized wild edible plants were cited by males than females, by key informants than generals, elders than youngsters, illiterate than literate, and poorer than other wealth class groups of the community. Priority rankings indicate that agricultural expansion, fuel wood harvest, overgrazing, and selective harvesting are the most threatening factors to underutilized wild edible plants. Conclusions Fifty underutilized wild edible plants, along with their associated indigenous knowledge, were recorded. Local people utilize them for supplementing staple food, as emergency food, to get relief, trust, and chew during drought. But they are mainly threatened by different human activities in the study area.